Hyponatremia in Acute Subarachnoid Hemorrhage: Frequency and Pathophysiology (Bangladesh Journal of Neuroscience, 2026)
Background: Hyponatremia is the most common electrolyte abnormality seen in patients with aneurysmal SAH. Clinically significant hyponatremia (Serum Sodium